Novel multi‐spectral short‐wave infrared imaging for assessment of human burn wound depth. - Nunez, Johanna; Mironov, Sergey; Wan, Bingchun; Hazime, Alaa; Clark, Audra; Akarichi, Chiaka; Abdelfattah, Kareem; Korlakunta, Sneha; Mandell, Samuel; Arnoldo, Brett; Chan, Rodney; Goverman, Jeremy; et al. (Wound Repair & Regeneration, 2024)
Burn depth determination is critical for patient care but is currently lacking accuracy. Recent animal studies showed that Short Wave Infrared (SWIR) imaging can distinguish between superficial and deep burns. This is a first human study correlating reflectance of multiple SWIR bands using a SWIR assessment tool (SWAT) with burn depth classifications by surgeons and histology. Burns and adjacent normal skin in 11 patients with thermal injuries were imaged with visual and narrow bands centred at 1200, 1650, 1940 and 2250 nm and biopsies were taken from select areas. Reflectance intensities for each band in 273 regions of interest (ROI) were divided by the normal skin reflectance and combined into three Reflectance Indices (RIs). In addition, burns in ROIs and biopsies were classified by five surgeons and three pathologists, respectively, as superficial partial, deep partial, or full thickness. Results show that for burn depth increase classified by the surgeons, reflectance increased at 1200 and 2250, decreased at 1940, and didn't change at 1650 nm. In contrast, all three RIs increase with burn depth and predict the deep and full depths ROIs representing operable regions (Area Under Curve >0.6507, p < 0.0001). Pathologists' classification matched surgeons' classification of burn category only in eight of 21 biopsies (38.1%), but reflectance at all bands and one RI for all deep partial and full thickness biopsies were larger than in non‐biopsy normal and superficial partial thickness ROIs (p < 0.0118). In conclusion, multi‐spectral imaging with a new SWAT is a promising approach for evaluation of burn wound depth.